Macrophage-mediated oxidation of extracellular low density lipoprotein requires an initial binding of the lipoprotein to its receptor. - M Aviram; M Rosenblat (Journal of Lipid Research, 1994)
Cells of the arterial wall including macrophages were shown to oxidize low density lipoprotein (LDL) in vitro. Upon incubation of LDL with J-774.A1 macrophage-like cell line for 18 h in the presence of 1 microM CuSO4, extensive macrophage-mediated oxidation of the LDL fatty acids and cholesterol moieties was demonstrated. Similar results were found with mouse peritoneal macrophages or human monocyte-derived macrophages. Several lines of evidence suggest that LDL binding to the LDL receptor on macrophages is required for the cell-mediated oxidation of LDL. 1) Incubation of the cells in the presence of monoclonal antibody to the LDL receptor (IgG-C7), substantially inhibited lipoprotein oxidation. 2) Pretreatment of LDL with monoclonal antibodies to the LDL receptor binding domains on the LDL apoB-100 (mAbs B1B6 and B1B3) inhibited cell-mediated oxidation of LDL by 52-95%. 3) Down-regulation of the macrophage LDL receptors (by preloading the cells with cholesterol) reduced LDL oxidation by 42%. 4) Up-regulation of the LDL receptor (by macrophage incubation in serum-free medium) was associated with 80% elevation in LDL oxidation. 5) Macrophage activation with lipopolysaccharide up-regulated the LDL receptors and was associated with up twofold increase LDL oxidation. 6) Human monocyte-derived macrophages from a patient with homozygous familial hypercholesterolemia, which lack the LDL receptor, failed to oxidize the LDL. 7) On using acetylated LDL or methylated LDL, which do not bind to the LDL receptor, macrophage-mediated oxidation of the lipoprotein did not occur. The binding of LDL to the macrophage LDL receptor under oxidative stress induced the oxidation of extracellular unbound LDL as demonstrated by cell-mediated lipid peroxidation of mAb B1B6-treated LDL by cells that were preincubated with native LDL. Furthermore, macrophage conditioned medium (MCM) that was obtained after 5 h of cells preincubation with native LDL under oxidative stress (1 microM CuSO4), followed by lipoprotein removal and a further 18 h of cell incubation (but not MCM that was similarly obtained without cell preincubation with LDL), was found to contain oxidized linoleic and arachidonic acids and was able to induce LDL lipids peroxidation. In conclusion, macrophage-mediated oxidation of LDL requires an initial binding of the lipoprotein to the LDL receptor on the cell surface under oxidative stress. This interaction leads to the formation and release of cellular oxidized polyunsaturated fatty acids that can oxidize the LDL molecule extracellularly.